ELL frontiers : using technology to enhance instruction for English learners - Parris, Heather; Estrada, Lisa; Honigsfeld, Andrea M. (Thousand Oaks : Corwin, 2017)
Your GPS for improving ELLs' academic outcomes This is not yesterday's ELL classroom. Thanks to the Common Core and other rigorous new standards, it's more challenging than ever to meet the needs of our English learners. But yesterday's classrooms didn't have the so many powerful digital tools at your immediate disposal. Written by three tech-savvy ELL experts and grounded in the latest research on English language and literacy development and technology integration, this timely book will serve as your go-to road map for navigating this exciting new frontier. Inside, you'll find:- An overview of current digital age learning experiences and trends- Step-by-step guides to implementing technology-infused lessons that are specifically aligned with English learners' needs, including a sample lesson seed in each chapter- Authentic vignettes of current uses of technology in the classroom- Professional Learning Network questions for group discussion Take a look for yourself. ELL Frontiers will give you the tools not only to improve academic outcomes and enhance language development, but also to cultivate digital citizenship.'By incorporating the best of digital age learning, the authors inspire practitioners to bring ELL instruction to the next level. ELL Frontiers shows how technology-enhanced instruction can elevate learning from our prior emphasis on'covering' material to'uncovering' English learners' rich experience and perspective.' -Jane Holmberg, Educational Consultant.
Includes bibliographical references and index.
Description based on XML content.
Keywords: English language -- Study and teaching -- Technological innovations; English language -- Study and teaching -- Computer-assisted instruction; English teachers -- Training of; English language -- Computer network resources; Language and languages -- Study and teaching; Second language acqusition; Applied linguistics